Critique of "An Evaluation of the Florida A-Plus Accountability Program" - Camilli, Gregory; Bulkley, Katrina (Education Policy Analysis Archives, 2001)
In 1999, Florida adopted the "A-Plus" accountability system, which included a provision that allowed students in certain low-performing schools to receive school vouchers. In a recently released report, An Evaluation of the Florida A-Plus Accountability and School Choice Program (Greene, 2001a), the author argued that early evidence from this program strongly implies that the program has led to significant improvement on test scores in schools threatened with vouchers. However, a careful analysis of Greene's findings and the Florida data suggests that these strong effects may be largely due to sample selection, regression to the mean, and problems related to the aggregation of test score results.